THE δ13C OF BIOGENIC METHANE IN MARINE SEDIMENTS: THE INFLUENCE OF CORG DEPOSITION RATE - Blair N. (My University, 1998)
The δ13C of biogenic methane produced in marine sediments ranges from -110 to -55%%. The isotopic composition of the methane (δ13CCH4) is constrained by the fraction of metabolized organic carbon converted to CH4. The flux of labile organic carbon into the seabed (JMOC) and the availability of oxidants (Aox), such as O2 and SO4=, dictate that fraction, i.e., proportionately more methane should be produced as the ratio JMOC/Aox increases. Chemical, physical (e.g., sediment resuspension) and biological (bioturbation and bioirrigation) processes determine Aox. Given that δ13CCH4 is always less than δ13C of the metabolizable organic carbon, δ13CCH4 should increase when JMOC and the portion of metabolized carbon converted to methane increase. A positive linear correlation (r2=0.92) is observed between δ13CCH4 and JMOC for a database containing four continental margin sites. When the pore water sulfate gradient (ΔSO4=/Δdepth) is used as a surrogate for JMOC, the data set is extended to 15 locations spanning all latitudes. A linear relationship between the sulfate gradient and δ13CCH4 (r2=0.98) for shelf/slope environments suggests that either JMOC or JMOC/Aox is the master variable that controls the 13C/12C content of the biogenic methane. Carbonate precipitation and/or a methanogenic back reaction may obscure the correlation in deep-sea sediments. Evidence for the relationship between δ13CCH4 and JMOC appears to be preserved in Miocene-age dolomitic deposits.
Keywords: δ; BIOGENIC METHANE; MARINE SEDIMENTS